Investigation on the effectiveness of progranulin as a novel predictive biomarker for allergic disorders - Nisreen Waleed Mustafa; Zaid Nabeel Elia; Abeer Mansour Abdel Rasool; Sanaria Fawzi Jarjes; Salam Farid Nawara; Shakhawan Hamid (Journal of Advanced Biotechnology and Experimental Therapeutics)
Progranulin (PGRN) has been implicated in the emergence of several inflammatory conditions. However, the function of PGRN in allergy-related conditions has not been clearly elucidated. Thus, the current study aimed to investigate the effectiveness of PGRN as a biomarker in allergic disorders. A total of 124 participants (84 with allergic disorders and 40 healthy individuals) were included in this study. Patients were divided into two groups, 38 were classified as having allergies related to the respiratory system and 46 with allergies related to the skin, based on their clinical diagnosis. This categorization was confirmed by serological diagnosis by estimating the levels of immunoglobulin E (IgE). Additionally, C-reactive protein (CRP) levels were measured for the detection of inflammation. Serum PGRN level was estimated by the enzyme-linked immunosorbent assay (ELISA) technique, while interleukin-6 (IL-6) concentration was determined by the fluorescent immunoassay technique. Serum PGRN levels were significantly increased (p>0.05) in all patient groups as compared with controls. Adult patients recorded a significant elevation in PGRN level (p0.05) was recorded in terms of disease type (respiratory tract and skin allergies) or gender. Additionally, the results of Spearman's correlation test revealed that there was no significant correlation between PGRN and each of IgE, CRP, and IL-6. Thus, the current study concluded that PGRN had efficacy as a predictive biomarker for various allergic disorders. [ J Adv Biotechnol Exp Ther 2025; 8(1.000): 116-124]